Model Pembelajaran Somatic, Auditory, Visualization, Intellectualy (SAVI) Berbantuan Icebreaker Terhadap Hasil Belajar IPA Siswa - I Kadek Peri Wijaya; Gede Wira Bayu; Made Sumantri (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
Students who are less enthusiastic in participating in learning both individually and in groups and the teacher's inability to apply learning models that can create interesting and fun learning. The purpose of the study was to analyze the Somatic, Auditory, Visualization, Intellectual (SAVI) learning model with the aid of an icebreaker on the science learning outcomes of class V students. This study was quasi-research with a non-equivalent post-test-only group design. This study used a population of all students of class V, which amounted to 128 people. Based on the random sampling technique, the sample was assigned to the experimental group, namely class V with 25 students, and the control group, namely class V with 25 students. The data collection method used is the test method, namely a multiple-choice test, totaling 30 questions. The data that has been collected is then processed with descriptive and inferential statistics. Based on the results of the study, it is known that the average science learning outcomes obtained by the experimental group are greater than the control group (18.34>15.78). The results of the t-test showed tcount 3,598 and ttable with a significance level of 5% obtained 2,021. Based on the test results tcount > ttable (3.598 > 2.021), so Ho is rejected and H1 is accepted. So, it can be concluded that there is a significant effect of the Somatic, Auditory, Visualization, Intellectualy assisted learning model with the help of icebreaker on the science learning outcomes of fifth-grade students.